The Relationship Between Caregiver Burden and Resilience and Quality of Life in a Turkish Pediatric Rehabilitation Facility - KARADAĞ SAYGI, NAİME EVRİM; KENİŞ COŞKUN, ÖZGE (ELSEVIER SCIENCE INC, 2020)
Purpose: To investigate the effect of caregiver burden, resilience, and quality of life of the parents of patients who are followed-up in a tertiary pediatric rehabilitation clinic. Design and methods: This is a correlational cross-sectional study. Parents of patients who attend to utilize pediatric rehabilitation outpatient clinics of a tertiary center on a regular basis were invited to participate. All participants filled in the Zarit Caregiver Burden (ZCB) scale, Family Resilience scale (FRS) and Nottingham Health Profile (NHP). Results: A total of 107 patient and caregiver dyads were included. Fifty-five (51%) patients had cerebral palsy, 10 (9%) had spina bifida and 42 (39%) had other neurodevelopmental disorders. Eighty-one (75%) of the caregivers were mothers. There was a significant difference in the caregiver burden between ambulatory children (Mean ZCB score 30.11 +/- 13.56) and non-ambulatory patients (Mean ZCB score 37.22 +/- 13.91) (p = .01). There were moderate negative correlations between caregiver burden and FRS commitment to life and FRS self-sufficiency subscales. Caregiver burden significantly positively correlated with all NHP domains. Conclusions: Caregiver burden is significantly higher in parents of non-ambulatory children when compared to ambulatory children in the pediatric rehabilitation setting. Caregiver burden and resilience correlated on moderate levels, but the factors influencing them are still unclear. Practice implications: Healthcare and social support should be given to all caregivers in pediatric rehabilitation setting, but more so to the caregivers of non-ambulatory patients. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: Caregiver burden; Pediatric rehabilitation; Resilience; Quality of life; CHILDREN; FAMILIES